The effectiveness of the Healthworks Staying Steady community-based falls prevention exercise programme to improve physical function in older adults: a 6-year service evaluation - Emily James; Paul Oman; Michael Ali; Paul Court; Stuart Goodall; Simon J. Nichols; Alasdair F. O'Doherty (BMC, 2022)
Abstract Background Falls prevention exercise programmes are evidence-based and recommended for improving physical function in older adults. However, few service evaluations exist to assess the effectiveness of community-delivered interventions in practice. Methods We conducted a six-year, retrospective evaluation of the community-delivered Staying Steady programme (Healthworks, United Kingdom). Staying Steady is a 27-week, tailored strength and balance programme delivered in a group setting (1-h, once/week) and at home (30-40 min, 2-3 times/week). Participants were referred by healthcare professionals, or self-referred, due to a history or risk of falling. Routinely collected outcome measures (30-s chair stand, Timed Up and Go, four-stage balance test, and patient reported outcomes; including 'fear of falling' and 'ability to manage health') were analysed. Factors associated with programme completion were reported. The intervention effect on physical function was analysed in subgroups: participants used arms to chair-stand or a walking-aid at both ('aided'), neither ('unaided'), or one assessment timepoint ('aided at baseline only' or 'aided at follow-up only'). Results There were 1,426 referrals; 835 (67.3%) participants enrolled on to the Staying Steady programme, 406 (32.7%) declined, 185 (13.0%) were inappropriately referred and excluded from analysis. After enrolling, 451 (54.0%) participants completed, and 384 (46.0%) dropped out. Chair stand performance improved in participants who were unaided (n = 264; median 2.0 [1.0, 4.0] repetitions; P < 0.001), or aided at baseline, follow-up or both (n = 170, P < 0.05). Timed Up and Go performance improved in the unaided (n = 387; median ˗3.1 [˗5.4, ˗1.4] s, P < 0.001), and aided at baseline only (n = 32; median ˗4.9 [˗10.8, ˗3.4] s, P < 0.001) groups. Four-stage balance performance improved (n = 295; median 1.0 [0.0, 1.0] points, P < 0.001). After programme completion, participants self-reported an improved ability to manage their health and daily activities, improved confidence, and a reduced fear of falling. Presence of chronic obstructive pulmonary disease, fear of falling, prescribed nutritional support, disability and social deprivation influenced non-completion of Staying Steady. Conclusions Completing Staying Steady improved physical function in older adults. Methods to encourage retention of participants from groups associated with low uptake and adherence should be investigated.